2020
DOI: 10.1101/2020.10.03.20206367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Violence, firearms, and the coronavirus pandemic: Findings from the 2020 California Safety and Wellbeing Survey

Abstract: IMPORTANCE: Violence is a significant public health problem that has become entwined with the coronavirus pandemic. Conditions that contribute to violence--poverty, unemployment, lack of available resources, isolation, hopelessness, and loss--have intensified and are further compounded by the recent surge in firearm sales, which is itself a risk factor for firearm-related harm. OBJECTIVE: To describe individuals' worry about violence for themselves and others in the context of the pandemic, pandemic-related un… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…Contrarily, the types of firearm-related deaths that increased were related to accidental shootings. Given that a recent survey study found that around 40% of individuals have been storing at least one firearm unlocked in their home during the pandemic 33 and that other reports have shown a spike in firsttime gun owners, 21 our results suggest that pandemic-related firearm ownership may be doing more harm to owners and their families during SAH than good. This suggests that the determination that firearm retailers are essential businesses may merit future discussion.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Contrarily, the types of firearm-related deaths that increased were related to accidental shootings. Given that a recent survey study found that around 40% of individuals have been storing at least one firearm unlocked in their home during the pandemic 33 and that other reports have shown a spike in firsttime gun owners, 21 our results suggest that pandemic-related firearm ownership may be doing more harm to owners and their families during SAH than good. This suggests that the determination that firearm retailers are essential businesses may merit future discussion.…”
Section: Discussionmentioning
confidence: 46%
“…Of these, 47,000 (43.0%) were first-time owners. 21 This may at least partially explain why Hatchimonji et al demonstrated that firearm-related injuries have persisted unabated throughout the pandemic 22 despite orders to SAH. Commentary from other US trauma centers has postulated that firearm violence is paradoxically increasing despite overall crime rates dropping during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic resulted in a change in the practice of individuals' gun storage. Due to the evolving and uncertain nature of the pandemic, some gun owners used less secure methods of gun storage ( Kraviz-Wirtz, Aubel, Schleimer, Pallin, & Wintemute, 2020 ). They kept guns at the ready, loaded up and/or unlocked, in the home.…”
Section: Implications For Policymentioning
confidence: 99%
“…Incluso en algunos estados como Pensilvania, las armerías fueron consideradas negocios esenciales, por lo que permanecieron abiertas durante el confinamiento (Hatchimonji et al, 2020). En California, se estima que 110 mil personas compraron un arma de fuego como respuesta a la pandemia, de los cuales 47 mil lo hicieron por primera vez (Kravitz-Wirtz et al, 2020). En las ciudades de Nueva York, Chicago, Baltimore y Los Ángeles, Shutherland et al (2020) hallaron un aumento promedio de 34.7% en la verificación de antecedentes para la compra de armas en comparación a 2019, con datos del Buró Federal de Investigaciones (fbi, por sus siglas en inglés).…”
Section: El Uso De Armas De Fuego Durante La Pandemiaunclassified